Evolutionary Game Simulation on Government Incentive Strategies of Prefabricated Construction: A System Dynamics Approach - Baoquan Cheng; Yuhu Wei; Wei Zhang; Xintao Zhou; Huihua Chen; Lipeng Huang; Jianling Huang; Xiaofang Kang (Complexity)
Prefabricated construction is a state-of-the-art construction technology of both socio-economic and environmental benefits, but sometimes, it is not welcome due to its high cost. Governments play an important role in deeply promoting prefabricated construction, but its effects are not clear. This paper developed a system dynamics model for investigating and simulating the impacts of government incentive strategies on prefabricated construction by considering the evolutionary game process between the government and contractors. Data of Shanghai, China, is collected for demonstration and validation of the developed simulation model. Results show that (1) the evolutionary stable strategy does not exist in static game process; (2) the rate of adopting prefabricated construction is affected by the level of penalties and subsidies; (3) dynamic incentive strategies can better improve the stability of the evolutionary game process; and (4) the rational range of incentive rate can be obtained. Findings of this study facilitate governments to formulate and improve the incentive strategies of prefabricated construction, thus boosting the development of construction industrialization.